Expression and inheritance of hypersensitive resistance to rice hoja blanca virus mediated by the viral nucleocapsid protein gene in transgenic rice - Lentini, Zaida; Lozano Potes, Iván; Tabares Z., Eddie; Fory Sánchez, L.F.; Domínguez, J.; Cuervo Ibáñez, Maritza; Calvert, Lee A. (2003)
Rice hoja blanca virus (RHBV) is a major virus disease of economic importance affecting rice in northern South America, Central America and the Caribbean. This is the first report of transgenic resistance to RHBV and the transformation of an indica rice variety from Latin America. Rice transformed with the RHBV nucleocapsid protein (N) gene had a significant reduction in disease development. Several reactions were observed that ranged from susceptible to completely resistant plants (immunity). The resistant reactions were characterized by the production of local lesions like a hypersensitive reaction or a recovery phenotype with the emergence of symptom-less new leaves. These transgenic RHBV-resistant rice lines expressed the N gene RNA at low levels that were below the detection limit by Northern blots and only resolved by RT-PCR. The nucleocapsid protein could not be detected in any of the transgenic plants either by Western or ELISA tests. These results suggest that the resistance encoded by the N gene in these plants appears to be mediated by RNA. When challenged with RHBV, the resistant transgenic lines showed a significant increased performance for important agronomic traits including the number of tillers, the number of grains per plant and the yield as compared to the susceptible control. Furthermore, upon inoculation some of the most-resistant transgenic lines showed agronomic traits similar to the uninoculated non-transgenic Cica 8 control. Using both agronomic traits and disease severity as criteria, several of the most-resistant lines were followed through the R4 generation and demonstrated that the N gene and RHBV resistance was inherited in a stable manner. These transgenic rice lines could become a new genetic resource in developing RHBV-resistant cultivars.